# Change each subtraction to addition of the opposite number, and then add. -8 - (-8)

*print*Print*list*Cite

The result of `-8 - (-8)` has to be determined.

`-8 - (-8)`

= `-8 + -(-8)`

Opening the brackets changes the sign of the term inside

= -8 + 8

= 0

**The result of -8 - (-8) = 0**

-8 -(-8)

According to this question, there are negative signs inside and outside brackets. Now according to the rule when a negative sign is multiplied by another negative we get a positive sign.

Like this;

- x - = +

- x + = -

+ x - = -

+ x + = +

Now as for the problem;

-8 - (-8)

= - 8 + 8

= 0

Hence Solved!

-8 - (-8)

There is always two ways you can think of this questions

1. Two negatives always make a positive! the negatives here would be the negative outside of the parentheses and the negative inside the parentheses so -8 **- (-**8) which will turn the equation into -8+8 = 0

2. The second way to think about it would be to add a 1 out side the paranthese and you will get negative one, -1, to multiply by -8 which will turn the -8 positive which will also give you the equation -8+8=0

Numbers of same values but different signs when added/subtracted is always equal to zero.

If you subtract a negative number, it is the same thing as addition. When you subtract a negative 8 from a negative 8, you are really adding 8 and negative 8. So, -8 + 8 will cancel out, making your answer 0.